A repertoire of failures in gudgeon pins for internal combustion engines, and a critical assessment of the design formulae. (May 2018) - Strozzi, A.; Baldini, A.; Giacopini, M.; Bertocchi, E.; Mantovani, S.
Abstract: The geometries commonly employed in gudgeon pins for internal combustion engines are examined. In particular, various methods for reducing the pin weight are considered. The selection of the appropriate clearance is addressed. The most typical failure modes are classified and interpreted in the light of stress analysis. The available approximate design formulae are assessed versus selected Finite Element forecasts. The fatigue cycles of stress and displacement related parameters are examined. The effect of the initial clearance on the contact pressure and on the pin ovalization is explored for selected clearance values. A typical Y –shaped fatigue crack is interpreted with the aid of Mohr circle. An error in a classical design approach based upon the containment of the pin ovalization is hypothesized. Highlights: several typical and uncommon failure modes of gudgeon pins are analyzed both analytically and numerically. analytical expressions for the pin stresses and comparisons with FE predictions are presented. a contradiction between fatigue cycles of displacement- and stress-related parameters for the pin ovalization is examined. a critical appraisal on a design formula against excessive pin ovalization is included. the influence of clearance is considered.